Myelopathy caused by Ossification of Thoracic Ligamentum Flavum - Farid Yudoyono; Rully Hanafi Dahlan; Sevline Esthetia Ompusunggu; Laniyati Hamijoyo; Muhammad Zafrullah Arifin (Indonesian Rheumatology Association, 2016)
Hypertrophy of the posterior spinal elements leading to compromise of the spinal canal and its neural elements is a well-recognized pathological entity affecting the lumbar or cervical spine. Such stenosis of the thoracic spine in the absence of a generalized rheumatological,metabolic, or orthopedic disorder, or a history of trauma is generally considered to be rare. Spinal ligaments, such as the ligamentum flavum (LF), are prone to degeneration and can lead to back pain and nerve dysfunction. Ossification of ligamentum flavum (OLF) is a pathological condition that cause neurological symptoms and usually occurs in the thoracic spine and less frequently in the cervical spine. However the disease is now being increasingly recognized as acause of thoracic myelopathy. We report a rare case of thoracic myelopathy caused by OLF. A 48-year-old male presented with a chief complaint of weakness of bilateral lower extremities. Neurological examination revealed sensory deficit at Th 11 level below. Magnetic resonance imaging and computed tomography demonstrated OLF at the right T9â€“11 level. Thoracicmyelopathy caused by OLF was consider and surgical intervention was performed. Posterior decompression and laminoplasty has been performed for this patient.Â Keywords: ossification of ligamentum flavum, thoracic myelopathy, laminoplasty